2014
DOI: 10.1542/peds.2013-1504
|View full text |Cite
|
Sign up to set email alerts
|

Building a Common Pediatric Research Terminology for Accelerating Child Health Research

Abstract: Longitudinal observational clinical data on pediatric patients in electronic format is becoming widely available. A new era of multiinstitutional data networks that study pediatric diseases and outcomes across disparate health delivery models and care settings are also enabling an innovative collaborative rapid improvement paradigm called the Learning Health System. However, the potential alignment of routine clinical care, observational clinical research, pragmatic clinical trials, and health systems improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…26 Without a common terminology, institutions may define the same clinical concept differently in EHRs. This makes combining data across research studies challenging because different definitions are used for the same underlying concepts.…”
Section: Pedsnet and Pediatric Big Datamentioning
confidence: 99%
See 1 more Smart Citation
“…26 Without a common terminology, institutions may define the same clinical concept differently in EHRs. This makes combining data across research studies challenging because different definitions are used for the same underlying concepts.…”
Section: Pedsnet and Pediatric Big Datamentioning
confidence: 99%
“…To address this need in pediatrics, PEDSnet and the National Institute of Child Health and Human Development have launched a pediatric research terminology initiative that is linking pediatric terms to existing standard terminologies. 26 …”
Section: Pedsnet and Pediatric Big Datamentioning
confidence: 99%
“…In 2011 the American Academy of Pediatrics (AAP) and NHLBI (National Heart and Blood Institute) published guidelines (1) for cholesterol and lipid screening for children (aged 9-11) and young adults (17)(18)(19)(20)(21). The guidelines were a bold step in the translation of the biologic concept of pediatric origins of adult cardiovascular disease (14) to clinical implementation and disease prevention.…”
Section: Exercise and Pediatric Origins Of Adult Disease-a Use Case Ementioning
confidence: 99%
“…Implementing key practices of "team science" (12), data interoperability, and terminology harmonization will be essential for the success of the initiatives. Child health researchers have led the scientific community in identifying ways to coalesce creative informatics approaches in multisite research (17), and in the creation of networks that integrate generalists and specialists that have immeasurably advanced child health in many areas (30).…”
Section: Child Health Focused Exercise Testing and Biomarker Discoverymentioning
confidence: 99%
“…Other domain communities, such as bioinformatics, have demonstrated that the process of creating agreed-on terminology can be adopted, can evolve, and can accelerate rapidly through crowdsourcing over a distributed infrastructure. 19,20 …”
Section: Materials Database Developmentmentioning
confidence: 99%